Numerical modelling on stimulated Brillouin scattering characterization for Graphene-clad tapered silica fiber - Lee H.J.; Abdullah F.; Ismail A. (EDP Sciences, 2023)
This paper presents finite numerical modelling on the cross-sectional region of tapered single mode fiber and graphene-clad tapered fiber. Surface acoustic wave propagation across the tapered surface region on tapered single mode fiber has a high threshold power at 61.87 W which is challenging to overcome by the incident pump wave. Surface acoustic wave propagation of fiber surface however made tapered wave plausible in the optical sensor application. This research introduces graphene as the cladding layer on tapered fiber, acoustic confinement occurs due to the graphene cladding which lowers the threshold power from 61.87 W to 2.17 W. The Authors, published by EDP Sciences, 2017.